Africa's Pulse, No. 19, April 2019 : An Analysis of Issues Shaping Africa’s Economic Future - Calderon, Cesar; Kambou, Gerard; Korman, Vijdan; Kubota, Megumi; Cantu Canales, Catalina (Washington, DC: World Bank, 2019)
Economic growth in Sub-Saharan Africa is estimated to have decelerated from 2.5 percent in 2017 to 2.3 percent in 2018, below the rate of growth of population for a fourth consecutive year. Regional growth in 2018 is below the pace projected in 2018 October issue of Africa's Pulse {0.4 percentage points lower). This slowdown was more pronounced in the first half of 2018 and it reflected weaker exports among the region's large oil exporters (Nigeria and Angola) due to dwindling oil production amid higher but volatile international prices for crude petroleum. A deeper contraction in Sudanese economic activity and a broad-based growth slowdown among non-resource-intensive countries also played a role.